Respuesta :
Answer:
let's start.
Step-by-step explanation:
[tex]\frac{(1+tanx)}{sinx} -secx = cscx\\[/tex]
we can write it as
[tex]\frac{(1 + tanx)}{sinx} = cscx + secx[/tex]
starting with left hand side
LHS
[tex]\frac{(1 + tanx)}{sinx}[/tex]
[tex]\frac{1}{sinx} + \frac{tanx}{sinx}\\\\cscx + tanx *\frac{1}{sinx}\\\\cscx + \frac{sinx}{cosx} *\frac{1}{sinx}\\\\cscx + \frac{1}{cosx}\\\\cscx + secx[/tex]
∴ LHS = RHS
hence, proved
Answer:
See below
Step-by-step explanation:
- (1 + tanx)/sinx - secx = cscx
- 1/ sinx + tanx/ sinx - 1/cosx = cscx
- 1/ sinx + sinx/ cosx × 1/sinx - 1/ cos x = cscx
- 1/ sinx + 1/cosx - 1/cosx = cscx
- 1/ sinx = cscx
- cscx = cscx